Biological, immunological and functional properties of two novel multi-variant chimeric recombinant proteins of CSP antigens for vaccine development against Plasmodium vivax infection - Shabani, S; Zakeri, S; Salmanian, A; Amani, J; Mehrizi, A; Snounou, G; Nosten, F; Andolina, C; Mourtazavi, Y; Djadid, N (Elsevier, 2017)
The circumsporozoite protein (CSP) of the malaria parasite Plasmodium vivax is a major pre-erythrocyte vaccine candidate. The protein has a central repeat region that belongs to one of repeat families (VK210, VK247, and the P. vivax-like). In the present study, computer modelling was employed to select chimeric proteins, comprising the conserved regions and different arrangements of the repeat elements (VK210 and VK247), whose structure is similar to that of the native counterparts. DNA encoding the selected chimeras (named CS127 and CS712) were synthetically constructed based on E. coli codons, then cloned and expressed. Mouse monoclonal antibodies (mAbs; anti-Pv-210-CDC and -Pv-247-CDC), recognized the chimeric antigens in ELISA, indicating correct conformation and accessibility of the B-cell epitopes. ELISA using IgG from plasma samples collected from 221 Iranian patients with acute P. vivax showed that only 49.32% of the samples reacted to both CS127 and CS712 proteins. The dominant subclass for the two chimeras was IgG1 (48% of the positive responders, OD492=0.777±0.420 for CS127; 48.41% of the positive responders, OD492=0.862±0.423 for CS712, with no statistically significant difference P>0.05; Wilcoxon signed ranks test). Binding assays showed that both chimeric proteins bound to immobilized heparan sulphate and HepG2 hepatocyte cells in a concentration-dependent manner, saturable at 80μg/mL. Additionally, anti-CS127 and -CS712 antibodies raised in mice recognized the native protein on the surface of P. vivax sporozoite with high intensity, confirming the presence of common epitopes between the recombinant forms and the native proteins. In summary, despite structural differences at the molecular level, the expression levels of both chimeras were satisfactory, and their conformational structure retained biological function, thus supporting their potential for use in the development of vivax-based vaccine.